Should Genetics Be Blamed for High Incidence of Uterine Disease in Dairy Cows? - Klibs N. Galvão; Christopher M. Seabury; Pablo Pinedo (EDIS, 2014)
Uterine diseases are highly prevalent in high-producing dairy cows. They have been associated with decreased pregnancy per artificial insemination (AI), extended interval to pregnancy, increased culling, and economic losses. This 3-page fact sheet presents the results of a recent paper that examined how alterations on the TLR genes, which control innate immune response, affect the susceptibility to uterine diseases. Written by Klibs N. Galvão, Christopher M. Seabury, and Pablo Pinedo, and published by the UF Department of Veterinary Medicine-Large Animal Clinical Sciences, May 2014.